Children's and adolescents' actual motor competence, perceived physical competence and physical activity: a structural equation modelling meta-analysis - Bourke, M.; Wang, H. F. W.; Wicks, H.; Barnett, L. M.; Cairney, J.; Fortnum, K. (Sports Medicine, 2025)
Background: Perceived physical competence (e.g. perceived motor skills, perceived athletic competence) is hypothesised to mediate the association between actual motor competence and physical activity in children, and this mediated association is expected to be stronger in older children and adolescents. However, no meta-analyses to date have synthesised the hypothesised mediation effect. Objectives: The purpose of this study was to systematically identify and synthesise the existing literature on the hypothesised mediation model between actual motor competence, perceived physical competence and physical activity in children and adolescents using structural equation modelling meta-analysis. Methods: Five electronic databases were searched from inception to December 2023 using a range of keywords for actual motor competence, perceived physical competence, physical activity and children/adolescents. Machine learning assisted screening was used to identify studies which reported the association between at least two of the variables in the hypothesised model in children and adolescents aged 4-18 years. One-stage structural equation modelling meta-analysis was used to test the hypothesised model. Moderation analysis was conducted to determine whether any of the model parameters differed as a function of children`s age. Results: A total of 218 reports that reported on 213 studies met the inclusion criteria and were included in the meta-analysis. Results from studies which examined the concurrent association between actual motor competence (gross motor, locomotion, object control), perceived physical competence, and physical activity demonstrated that perceived physical competence only had a small absolute (0.029 = r = 0.034) and relative (16.7-20.6% of total effect) mediating effect on the association between actual motor competence and physical activity. Results from studies which examined lagged associations (11% of included studies) also demonstrated a small bidirectional mediation effect of perceived physical competence. The moderation model demonstrated the mediation effect was significantly stronger in adolescents than children, albeit still weak. Conclusions: Perceived physical competence is not a strong mediator of the association between actual motor competence and physical activity in children and adolescents. Given that the association between perceived physical competence and actual motor competence with physical activity are largely independent, there may be benefits to targeting both motor skills and perceived physical competence to increase engagement in physical activity.